Comparative Study on the Effects of Organic fertilizer (Cow dung), Inorganic Fertilizer (N.P.K) and the Combined Effect of Fertilizers on the Growth Parameters of Strangler Fig (Ficus thonningii) - Garba, Ahmad Abdullahi; Imam, T. S. (Sahel Journal of Life Sciences FUDMA, 2024)
A comparative study on the effect of organic manure (Cow Dung), inorganic fertilizer (NPK 15-15-15), and their combined effect on the growth of Strangler fig (Ficus thonningii) was carried out at Government Senior Secondary School Dawakin Tofa Local Government Area, Kano State, Nigeria for 28 weeks. The objective of this study was to determine and compare the effect of organic fertilizer (Cow Dung), inorganic fertilizer (N.P.K 15:15:15) and their combined effects on the growth of Ficus thonningii seedlings. The experiment was laid out in a Randomized Complete Block Design (RCBD) with five treatments and a control replicated four times. The treatments consisted of T1= (15g NPK), T2 = (15g CD), T3 = (7.5g NPK: 7.5g CD), T4 = (11.3g NPK + 3.7g CD), T5 = (11.3g CD + 3.7g NPK) and a control (unfertilized) denoted as T6. Various growth parameters such as plant height, number of leaves, plant girth, leaf size and number of branches per plant were measured at 2-week intervals for 7 months. All the data collected were subjected to a two-way analysis of variance (ANOVA) at p<0.05 level of significance using R-software. The results from the experiment showed that most growth characters measured were significantly affected by the application of sole cow dung (15g CD). Thus, based on results obtained in this study, it is suggested to use 15g sole of cow dung for optimum and better growth of Ficus thonningii seedlings in the study area.